THEORETICAL PRINCIPLES OF APPLICATION OF PROJECT MANAGEMENT IN INNOVATIVE ACTIVITY (American Journal of Business Management, Economics and Banking, 2023)
This article describes the wide-ranging socio-economic changes and reforms taking place in the modern economy, the need to improve the activities of economic entities on the basis of modern mechanisms, current problematic issues, changes and occurrences in the conditions of market relations. that it is the demand of the times to anticipate the opportunities that may come, to develop economic policy and strategy, and to provide these changes with a new method, a new technique - technology. It is this term "innovation" that today is dedicated to the classification of "innovation", "innovative activity", "innovative projects".